Sex differences in parents' estimations of their own and their children's multiple intelligences: a portuguese replication - Felix Neto (2011)
In this study, 148 Portuguese adults (M = 45.4 years) rated themselves and their children on overall IQ and on H. Gardner (1999) 10 intelligence subtypes. Men's self-estimates were not significantly higher than women's on any of the 11 estimates. The results were in line with previous studies, in that both sexes rated the overall intelligence of their first male children higher than the first female children. Higher parental IQ self-estimates correspond with higher IQ estimates for children. Globally parents estimated that their sons had significantly higher IQs than their daughters. In particular, parents rated their son's spiritual intelligence higher than those of their daughters. Children's age and sex, and parents' age and sex were all non-significant predictors of the overall "g" score estimates of the first two children. Participants thought verbal, mathematical, and spatial intelligence were the best indicators of the overall intelligence for self and children. There were no sex differences in experience of, or attitudes towards, intelligence testing. Results are discussed in terms of the growing literature in the self-estimates of intelligence, as well as limitations of that approach.